Identifying key factors influencing mathematical visual thinking among pre-service mathematics teachers - Agus, Ria Noviana; Oktaviyanthi, Rina (Indonesian Journal of Educational Development (IJED), 2025)
Mathematical visual thinking is essential for understanding complex mathematical concepts, as it enables learners to interpret and connect visual and symbolic representations. However, many pre-service mathematics teachers struggle to integrate visual representations with algebraic expressions, leading to conceptual misunderstandings. This study aims to identify the key factors influencing mathematical visual thinking among pre-service mathematics teachers. A mixed-methods descriptive study was conducted, involving 150 students for quantitative analysis and 15 selected participants for qualitative interviews. Data were collected through a mathematical visual thinking test, a visual thinking factors questionnaire, semi-structured interviews, and document analysis of students’ mathematical tasks. The results indicate that most students exhibit moderate visual thinking ability (50%), with challenges in linking graphical and algebraic representations. The key influencing factors include teaching approaches (4.3), concept understanding (4.1), motivation (4.0), and technology use (4.2), whereas anxiety plays a lesser role (2.9). Students relying heavily on technological tools tend to improve accuracy but struggle with independent visualization. These findings suggest that instructional strategies should integrate structured visual exercises, emphasize transformation understanding, and balance technological support with manual problem-solving. This study provides new insights into enhancing visual thinking in mathematics and offers pedagogical recommendations for pre-service teacher education.